Inquiétants dépaysements : Les voyages mélancoliques de Germaine de Staël (1802-1814) - Stéphanie Genand (Viatica)
The Coppet group, a circle of thinkers around 1800, put displacement and the crossing of borders at the heart of its productions. Born out of a sense of national disaffiliation, the group plays a founding experimental role for the consciousness of the subject in travel narratives. Soliciting travel as much in the exploration of a country as in philosophy and knowledge, Germaine de Staël’s De l’Allemagne is both a travel narrative and a metaphysical breviary. In a tone close to autobiography, the author observes an inner region rather than a foreign country.